Implementasi Manajemen Sumber Daya (Biaya dan Prasarana) di Al-Hudz-Dzaq Islamic School - Hakim, Lukmanul; Aturrizqi, Lulu (Universitas Muhammadiyah Tangerang, 2024)
Educational facilities and infrastructure are one of several important resources in the progress of an institution. The aim of this study; 1) To describe the implementation of infrastructure management at the Al-Hudz-Dzaq Islamic School Islamic Education Foundation, 2) To describe the process of facilities and infrastructure management at the Al-Hudz-Dzaq Islamic School Islamic Education Foundation. The design of this research is qualitative descriptive research, research whose data is in the form of words originating from interviews, report notes, documents which prioritize description. This research concluded that the implementation of infrastructure management at the Al-Hudz-Dzaq Islamic School Islamic Education Foundation was carried out optimally and the process of management of educational facilities and infrastructure at the Islamic Education Foundation was carried out sequentially, starting from procurement planning, procurement, maintenance, inventory. and deletion so that it is always in a neat, orderly and orderly condition.ABSTRAKSarana dan prasarana pendidikan adalah salah satu dari beberapa sumber daya yang penting dalam kemajuan suatu lembaga. Penelitian ini bertujuan; 1) Untuk mendiskripsikan implementasi manajemen sarana prasarana di Yayasan Pendidikan Islam Al-Hudz-Dzaq Islamic School, 2) Untuk mendeskripsikan proses manajemen sarana dan prasarana di Yayasan Pendidikan Islam Al-Hudz-Dzaq Islamic School,. Desain penelitian ini adalah penelitian deskriptif kualitatif, penelitian yang data-datanya berupa kata-kata yang berasal dari wawancara, catatan laporan, dokumen yang didalamnya mengutamakan untuk pendiskripsian. Penelitian ini memperoleh kesimpulan bahwa, implementasi manajemen sarana prasarana di Yayasan Pendidikan Islam Al-Hudz-Dzaq Islamic School, dilakukan secara optimal dan proses manajemen sarana prasarana pendidikan di Yayasan Pendidikan Islam, dilaksanakan secara berurutan, dimulai dari perencanaan pengadaan, pengadaan, pemeliharaan, inventarisasi dan penghapusan agar selalu dalam kondisi rapih, tertib dan teratur.